Tanggung Jawab Korporasi dalam Penggunaan Tenaga Kerja Asing dalam Perpektif Kemanfaatan - Indra Yudha Koswara; Hana Faridah (Proceedings Series on Social Sciences & Humanities, 2025)
This article examines corporate responsibility in the use of foreign workers (TKA) from a utility perspective, focusing on how corporate regulations and practices align with the goal of legal utility, namely to provide optimal benefits for the company, the state, and society. The use of foreign workers is a necessity in the dynamics of globalization and industrial development, but it carries legal consequences that require corporations to comply with licensing requirements, technology transfer, protection of local workers, and fulfillment of the company's social function. Using a normative juridical approach, this article examines corporate obligations as stipulated in laws and regulations and assesses the extent to which monitoring and sanction mechanisms can create beneficial effects for all parties. The analysis shows that corporate responsibility, when carried out in a compliant and proportionate manner, not only provides legal certainty but also supports the improvement of the national workforce's competence, encourages healthy investment, and maintains social stability. Therefore, fulfilling corporate responsibility in the use of foreign workers is an important instrument for realizing legal benefits that balance economic interests and community protection.